2004
DOI: 10.1073/pnas.0405692101
|View full text |Cite
|
Sign up to set email alerts
|

Prohaptoglobin is proteolytically cleaved in the endoplasmic reticulum by the complement C1r-like protein

Abstract: Many secretory proteins are synthesized as proforms that become biologically active through a proteolytic cleavage in the trans-Golgi complex or at a later stage in the secretory pathway. Haptoglobin (Hp) is unusual in that it is cleaved in the endoplasmic reticulum before it enters the Golgi. Here, we present evidence that the recently discovered complement C1r-like protein (C1r-LP) mediates this cleavage. C1r-LP has not previously been shown to possess proteolytic activity, despite its homology to trypsin-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 26 publications
2
52
0
1
Order By: Relevance
“…16 Automated Edman degradation was performed by using an Applied Biosystems Model 477A sequencer (Applied Biosystems, Foster City, CA) with on-line phenylthiohydantoin analysis by high-performance liquid chromatography (HPLC; Model 120A; Applied Biosystems). In agreement with recent data demonstrating a very low degree of cleavage of recombinant Hp to ␣-and ␤-chains in 293 cells, 17 amino-terminal sequencing of recombinant Hp yielded only the sequence of the mature ␣-chain amino-terminus (VDSGNDVTDIAD). Two aminoterminal sequences in equimolar amounts were obtained for recombinant Hpr (LYSGNDVTDISD and ILGGHLDAKGSF).…”
Section: Study Design Expression and Purification Of Recombinant Hp1-supporting
confidence: 91%
“…16 Automated Edman degradation was performed by using an Applied Biosystems Model 477A sequencer (Applied Biosystems, Foster City, CA) with on-line phenylthiohydantoin analysis by high-performance liquid chromatography (HPLC; Model 120A; Applied Biosystems). In agreement with recent data demonstrating a very low degree of cleavage of recombinant Hp to ␣-and ␤-chains in 293 cells, 17 amino-terminal sequencing of recombinant Hp yielded only the sequence of the mature ␣-chain amino-terminus (VDSGNDVTDIAD). Two aminoterminal sequences in equimolar amounts were obtained for recombinant Hpr (LYSGNDVTDISD and ILGGHLDAKGSF).…”
Section: Study Design Expression and Purification Of Recombinant Hp1-supporting
confidence: 91%
“…In accordance with recent data showing that only a low degree of cleavage of recombinant proHp to the ␣-and ␤-chains takes place in 293 cells (19), amino-terminal sequencing showed that recombinant Hp remained largely uncleaved (14). However, the recombinant Hp bound to Hb has similar receptor binding activity as Hb in complex with native plasmaderived Hp (14).…”
Section: S-carboxyamidomethylated Cys-containing Peptides Further Supsupporting
confidence: 91%
“…In contrast, the primary translation product of mammalian Hp mRNA consists of a signal sequence, a CCP, and a SP domain. After the release of the signal sequence and while still in the endoplasmic reticulum, this polypeptide is cleaved between the two domains by C1r-like protein (19). Whether the difference in cleavage mechanisms between HpL and Hp has any physiologic significance remains to be studied.…”
Section: Discussionmentioning
confidence: 99%